Beyond Numbers: Determinants of Student Choice of Sharia Accounting Study Program in the Riau Islands - Hanum, Fauziah; Rahman, Aulia (Majapahit Journal of Islamic Finance and Management, 2025)
This study analyzes the influence of career prospects, social environment, and family environment on students' decisions to choose the Sharia Accounting Study Program in the Riau Islands. Data were obtained from 122 respondents and analyzed using PLS-SEM. The results indicate that career prospects and social environment have a significant positive effect, while family environment has no significant effect. These findings emphasize the importance of career prospects and social support in student decisions.